Pelatihan Manajemen Modern Berbasis Usaha Mikro di Negeri Passo Kota Ambon - Abednego, Abednego; Rumahlewang, Emma; Lokolo, Lambertus Johanes; Sahalessy, Arnold (Universitas Pattimura, 2025)
The background of modern management training based on micro-enterprises is that not all UMKM actors in Negeri Passo, Ambon City have implemented modern management properly. The purpose of this service is to increase the capacity of UMKM actors' human resources to have managerial competence. The focus of the training is all activities to provide, obtain, improve, and develop managerial competence. The focus of training is all activities to provide, obtain, improve, and develop managerial competencies. The activities are carried out in several stages, namely: (1) Situational analysis of MSMEs is carried out to determine the steps for identifying needs; (2) The activity planning stage includes the preparation of the syllabus and activity schedule; (3) the training implementation stage: the training is carried out for one day, namely on Monday, March 10, 2025, at 09.00 WIT until finished. The activities are carried out with 2 sessions, namely the first session providing material, in the form of information about managerial competencies and the second session in the form of group discussions; (4) sustainability plan: formation of MSME groups and mentoring. This community service activity has succeeded in improving managerial abilities and skills among UMKM actors. The impact felt is increasing self-confidence in doing business.